POST-EXTUBATION HIGH-FLOW NASAL CANNULA THERAPY IN SEVERE POSTOPERATIVE NEUROSURGICAL PATIENTS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of high-flow nasal cannula (HFNC) therapy immediately after extubation and to identify factors associated with HFNC failure in severe postoperative neurosurgical patients.Methods: A prospective observational study was conducted in 60 severe postoperative neurosurgical patients who received HFNC immediately after extubation. Clinical variables, arterial blood gas values, Airway Care Score (ACS), and chest radiography findings were recorded before extubation. Patients were followed for 72 hours after extubation to detect respiratory failure and HFNC failure. HFNC failure was defined as the need for reintubation or rescue noninvasive ventilation (NIV) because of respiratory deterioration.Results: HFNC failure occurred in 14 of 60 patients (23.3%); all eventually required reintubation. The failure group had a significantly higher rate of pulmonary infiltrates on chest radiographs than the success group (57.1% vs. 15.2%) and significantly higher ACS values (p < 0.001). No significant between-group differences were observed in PaO₂/FiO₂ ratio, PaCO₂, respiratory rate, Glasgow Coma Scale score, or duration of mechanical ventilation before extubation. Rescue NIV was attempted in four patients in the failure group, but all failed because of poor cooperation and impaired airway protection.Conclusion: In severe postoperative neurosurgical patients receiving HFNC immediately after extubation, the failure rate was 23.3%. Pulmonary infiltrates on chest radiography and higher ACS values were associated with HFNC failure in univariable analysis. HFNC may be considered a feasible post-extubation respiratory support strategy in this population; comparative studies with multivariable analyses are needed to better define its effectiveness and independent prognostic factors.
Keywords: High-flow nasal cannula; neurosurgery; post-extubation respiratory failure; airway care.